Software and instrument improvements reduced significantly navigation acquisition time in computer assisted TKA: A cadaveric study. Issue 1 (1st January 2017) - Lampe, Frank; Marques, Carlos J.; Lützner, Jörg
Abstract: Purpose : Computer navigation in total knee arthroplasty (TKA) has proven to significantly reduce the number of outliers in prosthesis positioning and to improve mechanical leg alignment. Despite these advantages the acceptance of navigation technologies is still low among orthopaedic surgeons. The time required for navigation might be a reason for the low acceptance. Objective : The aim was to test whether software and instrument improvements made in an established navigation system could lead to a significant navigation acquisition time reduction. Materials and methods : An improved and the current version of the TKA navigation software were used to perform surgery trials on a human cadaveric specimen by two experienced orthopedic surgeons. Results : A significant effect of the "procedure" (navigation software version) on the navigation time ( p  < 0.001) was found, whereas the difference between surgeons was not significant ( p  = 0.2). There was no significant interaction between surgeon and navigation software version ( p  = 0.5). The improved version led to a significant navigation acquisition time reduction of 28%. Conclusions : Software and instrument improvements led to a statistically significant navigation acquisition time reduction. The achieved navigation acquisition time decrease was independent from surgeon. Specific instrument and software improvements in established navigation systems may significantly decrease the surgery time segments where navigation takes place. However, the total navigation acquisition time is low in comparison to the total surgery time.